2009
DOI: 10.3109/00365510903484063
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, visfatin, insulin resistance, and body composition change in chronic obstructive pulmonary disease

Abstract: These results may be earlier signs for further diseases that can emerge in the advanced stages in patients with COPD. Evaluating the patients not only with the pulmonary function and also systemically, contributes to minimizing the mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
2
24
1
2
Order By: Relevance
“…In addition, plasma leptin levels in COPD patients were correlated with BMI, lean body mass, FEV 1 and IC. Similar to our results, Eker et al (15) as well found leptin levels to be lower in the COPD group versus the control group, and determined a positive correlation between leptin levels and BMI. These results suggest that leptin levels are lower in patients with progressive airway obstruction, and decreased inspiratory capacity in other words with enhanced hyperinflation, and that decreased plasma leptin levels might be Table 4.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, plasma leptin levels in COPD patients were correlated with BMI, lean body mass, FEV 1 and IC. Similar to our results, Eker et al (15) as well found leptin levels to be lower in the COPD group versus the control group, and determined a positive correlation between leptin levels and BMI. These results suggest that leptin levels are lower in patients with progressive airway obstruction, and decreased inspiratory capacity in other words with enhanced hyperinflation, and that decreased plasma leptin levels might be Table 4.…”
Section: Discussionsupporting
confidence: 93%
“…Many recent studies have reported the relationship between leptin and local or systemic inflammation. Some studies [16,17,18,19,20] suggested that leptin may play an important role in the mechanism of weight loss in COPD patients and might be a potential biomarker to reflect the clinical status of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced energy turnover may be exacerbated by reduced insulin sensitivity in COPD [6]; insulin driving cellular glucose uptake via the GLUT-4 receptor [7]. Understanding mechanisms underlying these changes may lead to treatments to improve exercise capacity in patients with COPD.…”
mentioning
confidence: 99%